Una nueva especie de Pinguicula (Lentibulariaceae) del estado de Oaxaca, México - Zamudio Ruiz, Sergio; Salinas T., Antonio (Instituto de Ecología, A.C., 1996)
Pinguicula mirandae sp. nov. from the Tehuacan-Cuicatlan region in the state of Oaxaca is described and illustrated. It belongs to section Heterophyllum, subgenus Isoloba. It differs from the remaining species of this group by its subisolobed corolla with geniculate tube, and obovate-spathulate leaves.